PARALLEL CONSTRUCTIONS IN ENGLISH AND UZBEK PROVERBS - Nigorakhon Rakhimovna, Ruzibaeva (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study investigates the use of parallel constructions in English and Uzbek proverbs, aiming to uncover their linguistic structures, stylistic functions, and cultural significance. It explores how parallelism reflects the values, worldviews, and traditions embedded within the two distinct linguistic and cultural systems. Method: Employing a comparative methodology, the research analyzes a diverse corpus of proverbs from both English and Uzbek sources through linguistic and cultural perspectives. Results: The findings reveal both convergences and divergences in the use of parallel constructions, demonstrating their function in enhancing rhythm, aesthetic appeal, and rhetorical effect. Moreover, the analysis underscores how such constructions mirror cultural priorities and language-specific tendencies in proverbial expression. Novelty: This research presents an original and comprehensive comparative analysis of parallel structures in English and Uzbek proverbs—an area that remains underexplored—thereby contributing valuable insights into their structural features and cultural foundations.